Human capital, social capabilities and economic growth - Muhammad Ali; Abiodun Egbetokun; Manzoor Hussain Memon (Economies, 2018)
Theoretically, human capital is conclusively believed to be positively related with economic growth. While empirically, the said relationship does not always hold for several reasons. Thus, the current paper presents new results on a set of conditions under which human capital is robustly and positively associated with economic growth. Using data for 132 countries over 15 years, the empirical results reveal that human capital plays a positive role in per capita GDP growth only in the presence of better economic opportunities and high-quality legal institutions. In fact, economic opportunities reinforce the effect of human capital on growth: the easier it is to do business and trade domestically or internationally, the stronger the effect of human capital on growth. In conclusion, the findings suggest that inconclusive results in previous empirical studies on human capital and growth might be due to omitted variable bias as these studies do not include variables related to social capabilities.
Keywords: O15; O4; 330; human capital; economic growth; economic opportunities; social capabilities